El Niño Southern Oscillation influence on the Asian summer monsoon anticyclone - X. Yan; X. Yan; P. Konopka; F. Ploeger; M. Tao; R. Müller; M. L. Santee; J. Bian; J. Bian; M. Riese (Atmospheric Chemistry and Physics, 2018)
We analyse the influence of the El Niño Southern Oscillation (ENSO) on the atmospheric circulation and the mean ozone distribution in the tropical and subtropical UTLS region. In particular, we focus on the impact of ENSO on the onset of the Asian summer monsoon (ASM) anticyclone. Using the Multivariate ENSO Index (MEI), we define climatologies (composites) of atmospheric circulation and composition in the months following El Niño and La Niña (boreal) winters and investigate how ENSO-related flow anomalies propagate into spring and summer. To quantify differences in the divergent and non-divergent parts of the flow, the velocity potential (VP) and the stream function (SF) are respectively calculated from the ERA-Interim reanalysis in the vicinity of the tropical tropopause at potential temperature level θ = 380 K. While VP quantifies the well-known ENSO anomalies of the Walker circulation, SF can be used to study the impact of ENSO on the formation of the ASM anticyclone, which turns out to be slightly weaker after El Niño winters than after La Niña winters. In addition, stratospheric intrusions around the eastern flank of the anticyclone into the tropical tropopause layer (TTL) are weaker in the months after strong El Niño events due to more zonally symmetric subtropical jets than after La Niña winters. By using satellite (MLS) and in situ (SHADOZ) observations and model simulations (CLaMS) of ozone, we discuss ENSO-induced differences around the tropical tropopause. Ozone composites show more zonally symmetric features with less in-mixed ozone from the stratosphere into the TTL during and after strong El Niño events and even during the formation of the ASM anticyclone. These isentropic anomalies are overlaid with the well-known anomalies of the faster (slower) Hadley and Brewer–Dobson circulations after El Niño (La Niña) winter. The duration and intensity of El Niño-related anomalies may be reinforced through late summer and autumn if the El Niño conditions last until the following winter.